Dairy cow behaviour around calving: Its relationship with management practices and environmental conditions - Matamala, Fabiola; Strappini, Ana; Sepúlveda-Varas, Pilar (Austral Journal of Veterinary Sciences, 2021)
Calving is one of the most challenging and painful experiences for dairy cattle and a process that involves coping with physical and physiological changes, as well as environmental and management-related stressors. In recent years, it has been argued that the application of cow behaviour knowledge might facilitate their efficacious management during calving. This review aims to summarise and discuss current knowledge regarding the behavioural changes that occur around calving time. The relationship between calving behaviour, management practices, and environmental conditions in dairy cattle raised in intensive indoor production systems, as well as pasture-based systems, is also discussed. First, we briefly outline the process of parturition and the concept of maternal behaviour. We then describe behavioural changes that occur around parturition in normal and dystocic births and how variations in these behaviours can be used to predict normal or assisted calving in dairy cattle; particular emphasis is placed on the role of feeding, rumination, and lying behaviour. Finally, we review how management practices and environmental conditions can influence cow's behaviour at calving and discuss the importance of providing an environment that accommodates the behaviour they are motivated to perform. This review presents evidence that the time a cow is moved to the calving area, the type of group housing and the provision of a secluded area to calve, can impact the behavioral responses of dairy cows at calving. Evidence regarding the effects of exposure to environmental conditions such as heat during summer, and/or cold, wet and mud during winter can also have a negative impact on behaviour, suggesting potential benefits of providing cows with a protected area to calve. We conclude that a better understanding of the behaviour of parturient cows may help producers improve the care and management around calving time.